2012
DOI: 10.2176/nmc.52.747
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Chondrosarcoma of the Orbit

Abstract: A 20-year-old woman presented with a rare case of intraorbital mesenchymal chondrosarcoma manifesting as a 6-month history of progressive ptosis and exophthalmos of her left eye. Computed tomography and magnetic resonance imaging revealed a partially calcified round mass occupying the postbulbar space. Partial removal of the tumor via a left fronto-orbital approach was performed. The histological diagnosis was mesenchymal chondrosarcoma, and additional intraorbital exenteration was performed. Neither chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Clinically, orbital chondrosarcoma patients mainly present with progressive proptosis often developing over months to years, as seen generally in our patients 5, 7. Less frequent symptoms include: pain of variable severity, diplopia and impaired vision while ptosis, lacrimation and nasal obstruction were less consistently described 5, 7, 11. One of our patients described painful eye movements as shown in Table 1.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Clinically, orbital chondrosarcoma patients mainly present with progressive proptosis often developing over months to years, as seen generally in our patients 5, 7. Less frequent symptoms include: pain of variable severity, diplopia and impaired vision while ptosis, lacrimation and nasal obstruction were less consistently described 5, 7, 11. One of our patients described painful eye movements as shown in Table 1.…”
Section: Discussionsupporting
confidence: 65%
“…Orbital MCS was first described by Cardenas-Ramirez in 1959 4 . Subsequently, reports of orbital involvement by this neoplasm were published reaching 28 cases mentioned in the English-written literature mostly in adults 5 . As the orbit is a rare site of mesenchymal chondrosarcoma, here we report 3 pediatric cases with primary orbital MCS.…”
Section: Introductionmentioning
confidence: 75%
“…Even if radical resection is not performed in the first surgery, the patient’s outcome could improve if the tumors were removed with safety margins in the multiple surgeries. 19) In the current case, if we had removed his tumor with safety margins less than 84 months after initial surgery, the tumor might not have recurred.…”
Section: Discussionmentioning
confidence: 70%
“…It has been reported that a series of intraorbital MC patients had good outcomes after radical removal of their tumors. 19) However, the most difficult problem is the decision to determine the appropriate timing of total removal with minimal neurological deficit. Even if radical resection is not performed in the first surgery, the patient’s outcome could improve if the tumors were removed with safety margins in the multiple surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 MCS tends to develop in young patients in their second or third decades of life, with a female predominance. 14,19,21 The age at presentation ranges from 9 to 39 years, although there are some reports in congenital 11 or middle-aged patients, 18,19 with most cases occur between 10 and 30 years of age. 11,14 MCS of the orbit mainly affects female patients, 11 and our study, which included three females and two males, supports this finding.…”
Section: Discussionmentioning
confidence: 99%